Exercising the right to social protest as a mechanism for the defense of human rights: analysis of the Colombian socio-legal context in times of pandemic - Pereira Ortega, Duanys Liesel; Peñaloza Nuñez, Sharith Melissa (DIXI, 2022)
In Colombia, as of April 28, 2021, multiple demonstrations and social protests have been carried out in defense of human rights, in opposition to the tax reform and different actions of the State. In the context of these events, it is necessary to analyze the socio-legal context of the exercise of the right to social protest as a mechanism of defense and guarantee of protection of other human rights, during the covid-19 pandemic, since these spaces generate social agglomeration, which has been considered a risk factor in the face of the public health crisis. Based on the above, this article presents as a result an analysis of the problem addressed, derived from the legal conditions established by Colombian law and international humanitarian law, regarding the guarantee of the right to social protest and its related rights. The general objective is to analyze the Colombian socio-legal context of the exercise of the right to social protest as a mechanism for the defense of human rights in times of pandemic. This will be developed through a qualitative and descriptive methodology with a documentary research technique.